1996
DOI: 10.1126/science.271.5253.1282
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Fidelity of 3TC-Selected Mutant HIV-1 Reverse Transcriptase

Abstract: Monotherapy with (-)2',3'-dideoxy-3'-thiacytidine (3TC) leads to the appearance of a drug-resistant variant of human immunodeficiency virus-type 1 (HIV-1) with the methionine-184 --> valine (M184V) substitution in the reverse transcriptase (RT). Despite resulting drug resistance, treatment for more than 48 weeks is associated with a lower plasma viral burden than that at baseline. Studies to investigate this apparent contradiction revealed the following. (i) Titers of HIV-neutralizing antibodies remained stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
226
5

Year Published

1996
1996
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(244 citation statements)
references
References 50 publications
13
226
5
Order By: Relevance
“…Wainberg et al reported that an M184V substitution leads to an increase in fidelity of HIV-1 RT in vitro, which is accompanied by a decrease in rates of mutations in virions with such a mutated RT [37]. Pandey et al reported that the mutation M184V results in an increase in the fidelity of DNA synthesis, whereas the mutant M184A retains the low fidelity [38].…”
Section: Discussionmentioning
confidence: 99%
“…Wainberg et al reported that an M184V substitution leads to an increase in fidelity of HIV-1 RT in vitro, which is accompanied by a decrease in rates of mutations in virions with such a mutated RT [37]. Pandey et al reported that the mutation M184V results in an increase in the fidelity of DNA synthesis, whereas the mutant M184A retains the low fidelity [38].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that most patients with phenotypic YMDD-mutant HBV appear to fare better clinically than patients with wild-type hepatitis B infections, as assessed by HBV DNA levels and biochemical assessments, provides some reassurance regarding the value of continuing lamivudine in patients who maintain at least partial virological and clinical responses. This relative clinical benignity of YMDD-variant HBV in immunocompetent patients may be explained by the observations that YMDD variants of HIV 18 and HBV 10,19 are less replication competent in vitro than their wild-type counterparts. Finally, in 2 patients with YMDD-variant HBV, we observed durable HBeAg seroconversion.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Although lamivudine has a strong antiviral effect, the development of a resistant strain of virus presented a serious problem. 32 Lamivudine-resistant HIV was revealed to have amino acid substitutions in the YMDD motif of reverse transcriptase, 20,[33][34][35] and recently these substitutions have also been reported in HBV. [14][15][16][17] In addition, other mutations (phenylalanine [F]-to-L at amino acid 501 or an L-to-M substitution at amino acid 515) have been described in the B-domain of reverse transcriptase 18 of HBV during lamivudine and famciclovir treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The YMDD motif is one of the highly conserved domains in RNAdependent DNA polymerase present in retroviruses, hepadnaviruses, retrotransposons, group II intron, bacterial retrons, and the catalytic subunit of telomerase, and is involved in nucleotide binding in the catalytic site of the polymerase. [18][19][20][21][22][23] Amino acid substitutions in this motif were also associated with the resistance of HIV to other nucleoside analogues, such as ddC and FTC (5-fluoro-derivative of lamivudine). 21 Emergence of resistant viruses to nucleoside analogues has stimulated a heightened interest in the study of the YMDD motif, and more appropriate knowledge of HBV drugresistance patterns to lamivudine is considered imperative in improving patient management.…”
mentioning
confidence: 99%